Surgical treatment of obesity and excess risk of developing heart failure in a controlled cohort study - Christina E. Lundberg; Shabbar Jamaly; Martin Adiels; Jesper Lagergren; Carl Johan Svensson; Lena Björck; Annika Rosengren (ESC Heart Failure)
Abstract Aim We aim to assess the risk of heart failure in patients with obesity with and without gastric bypass surgery compared with population controls. Methods and results This cohort study included all patients aged 20–65 years with a first ever registered principal diagnosis of obesity in the Swedish Patient Register in 2001–2013. These patients were matched by age, sex, and region with two population controls from the general Swedish population without obesity diagnosis. The obesity cohort was divided into two groups: 27 882 patients who had undergone gastric bypass surgery within 2 years of obesity diagnosis and 39 564 patients who had not undergone such surgery. These groups were compared with 55 149 and 78 004 matched population controls, respectively. Cox regression provided hazard ratios (HR) with 95% confidence intervals (CI), adjusted for age, education, and sex. During follow‐up (maximum 10 years, median 4.4 years, and interquartile range 2.5–7.2 years), 1884 participants were hospitalized for heart failure. Compared with population controls, gastric bypass patients had no excess risk of heart failure during the initial 0–≤4 years of follow‐up (HR = 1.35 [95% CI = 0.96–1.91]) but a marked increased risk during the final >4–10 years of follow‐up (HR = 3.28 [95% CI = 2.25–4.77]). Non‐operated patients with obesity had a marked excess risk of heart failure throughout the study period compared with population controls. Conclusions Gastric bypass for obesity seems to reduce the risk of heart failure to levels similar to the general population during the initial 4 years after surgery, but not thereafter.